2023
DOI: 10.1021/acsami.3c12800
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast-Inspired Carrier Circulation for Improved Photoelectrochemical Photodetectors Based on Ti2CTx Nanosheets

Ruiyang Yu,
Hui Qiao,
Gengcheng Liao
et al.

Abstract: Here, a photoelectrochemical (PEC) photodetector with good flexibility and high photoresponsivity was successfully fabricated in a vertical structure, where the MXene (Ti2CT x ) nanosheet and carbon black electrode were separated by adenosine triphosphate/nicotinamide adenine dinucleotide phosphate (ATP/NADPH)-incorporated solid-state electrolyte. The photocurrent and photoresponsivity can reach 1.84 μA/cm2 and 8.89 μA/W, respectively, under a light intensity of 90 mW/cm2 at a bias potential of 0.6 V, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Compared to the other inorganic materials including the bismuth-based and other well-investigated 2D material-based PEC-type photodetectors, the Bi 13 S 18 I 2 PEC-type photodetector exhibited much superior photodetection performance in terms of responsivity and response time (Table S2). , One possibility for the excellent performance might be derived from the high quality, including high purity, continuous surface morphology, and relatively strong adhesion of the films on the substrate, of Bi 13 S 18 I 2 thin films synthesized by mist CVD.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the other inorganic materials including the bismuth-based and other well-investigated 2D material-based PEC-type photodetectors, the Bi 13 S 18 I 2 PEC-type photodetector exhibited much superior photodetection performance in terms of responsivity and response time (Table S2). , One possibility for the excellent performance might be derived from the high quality, including high purity, continuous surface morphology, and relatively strong adhesion of the films on the substrate, of Bi 13 S 18 I 2 thin films synthesized by mist CVD.…”
Section: Resultsmentioning
confidence: 99%
“…For the photodetector's counter electrode, a homogeneous blend of 0.5 mg conductive carbon black was dissolved in 1 mL of NMP solution. 8 The subsequent steps were identical to those used to create the anode electrode. The flexible ITO electrode pairs were then dried for 12 h at 60 °C in a vacuum oven before being stored for subsequent usage.…”
Section: Preparation Of Photoanode Electrodes and Countermentioning
confidence: 99%
“…Due to their unique structure and properties, low-dimensional materials, including two-dimensional 1 (2D), one-dimensional (1D), and zero-dimensional (0D) materials, have significant potential for use in electrical and optoelectronic applications. 2−5 In particular, 1D (such as nanowires and nanorods) and 2D 6 (such as transition-metal dichalcogenides and MXenes 7,8 ) materials have shown excellent performance in flexible devices, field-effect transistors, and photodetectors. 9−12 Nanostructured Te and Se, as well as their heterojunctions and alloys, are a novel class of low-dimensional materials that have enormous promise for use in photodetectors, laser therapy, and energy storage and conversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, MXene nanosheets were utilized as photoanodes to construct a PEC-type PD having fast response and decay times of 1.26 and 3.27 s, respectively . Yu et al reported that an MXene nanosheet and a conductive carbon black electrode were used to prepare a solid-state PEC-type PD device with adenosine triphosphate/nicotinamide adenine dinucleotide phosphate incorporation into an ionic gel electrolyte …”
Section: Introductionmentioning
confidence: 99%